Gambaran tingkat pengetahuan mahasiswa program profesi terhadap pengelolaan perilaku anak (Laporan Penelitian) - Monica Silvia Lay; Arianne Dwimega; F. Loes Djimahit Sjahruddin (Jurnal Kedokteran Gigi Terpadu, 2022)
Management of children’s behavior is an important component in dental practice in order to achieve successful treatment. Professional program students with a good knowledge level are expected to be able to manage children’s behavior appropriately so that they can provide dental care with good quality. Purpose: To assess the knowledge of professional program students of Faculty of Dentistry, Trisakti University regarding the management of children’s behavior in dental care. Methods: This was a descriptive observational study using cross-sectional research design. Data was collected using google form with a questionnaire that has been tested for validity and reliability. The sample consisted of 100 professional program students who met the inclusion criteria and agreed to the informed consent. This research has been approved by the Ethics Commision of the Faculty of Dentistry, Trisakti University with research no. 515/S1/KEPK/FKG/8/2021. Results: The results of the study were grouped into three categories of knowledge levels, that are good, quite good, less good. The results were found that 53 respondents (53%) have a good level of knowledge, 32 respondents (32%) with a quite good level of knowledge, and 15 respondents (15%) with a poor level of knowledge. Conclusion: The level of knowledge of most professional program students of the Faculty of Dentistry, Trisakti University regarding the management of children’s behavior in dental care is in the good category. However, students are also expected to increase their knowledge.